Iceland : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews economic developments in Iceland during 1990-95. It describes developments in the real economy, and examines monetary and exchange rate developments and policies and the transmission of monetary policy. The paper provides a detailed look at budgetary outcomes and the stance of fiscal policy for 1995. Determinants of past and present growth in Iceland are examined. Indicators of fiscal sustainability are used to argue for better public finances in Iceland. The paper also examines the Icelandic tax structure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet